Teacher’s Workload in Relation to Burnout and Work Performance - Magtalas, Santi A.; Eduvala, Joy C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Teaching is a rewarding yet demanding profession. While it brings immense joy when teachers experience fulfillment from achieving their goals, the wide range of responsibilities it entails can lead to exhaustion. This descriptive-correlational study explored the relationship between teachers' workloads, burnout levels, and work performance of permanent elementary school teachers from the Masinloc District, Division of Zambales. Using standardized instruments and the teachers’ Individual Performance Commitment and Review Form (IPCRF) ratings, data gathered were analyzed using descriptive and inferential statistics. The findings showed that teachers reported a high perception of work/role overload and experienced significant burnout, particularly regarding career satisfaction and attitudes toward students. Moreover, a strong positive relationship was found between burnout levels and work/role overload. Despite these challenges, teachers maintained high performance, which can be attributed to their dedication and commitment to their profession.